PENGUATAN ORIENTASI HAK-HAK REPRODUKSI DENGAN PENDEKATAN TAFSIR TRANSFORMATIF DI MA’HAD AL-QUR’AN UNIVERSITAS PTIQ JAKARTA - Abd. Muid Nawawi; Hamdani Anwar; St. Nurhafisah; Darwis Hude; Iwan Satiri; Teguh Arafah Julianto (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Women are often considered secondary creatures so that they do not have rights to themselves and the right to regulate themselves, especially in terms of reproductive rights. Reproductive rights are part of human rights which are often denied in society and often suffer from abuse and violence. This research uses a qualitative approach to better understand reproductive rights according to Masdar Farid Mas'udi with a transfarmative interpretation approach. As for the results of this research, in Masdar Farid Mas'udi's thoughts on women's reproductive rights, he divided them into several aspects, namely women's rights in choosing a partner, women's rights in enjoying sexual relations, women's rights in determining pregnancy or having offspring, women's rights in caring for children, women's rights to obtain reproductive leave, and women's rights to divorce their partners